RETRACTION: Major phosphorus in soils is unavailable, yet critical for plant development - Beckley IKHAJIAGBE; Geoffrey O. ANOLIEFO; Ogochukwu F. OLISE; Fabian RACKELMANN; Milena SOMMER; Isaac J. ADEKUNLE (Notulae Scientia Biologicae, 2024)
This review article (Ikhajiagbe et al., 2020) has been retracted at the request of the editors-in-chief and authors, following the identification of a similarity between a portion of this article and a previous work (Shen et al., 2011), which was not detected by anti-plagiarism software before publication. The first author apologizes to the editors and readers, as well as to the authors of the original work, for the unfortunate incidence of plagiarism and the unfortunate circumstances that occurred (Appendix 1).